2015
DOI: 10.1146/annurev-phyto-080614-120224
|View full text |Cite
|
Sign up to set email alerts
|

Genomics Spurs Rapid Advances in Our Understanding of the Biology of Vascular Wilt Pathogens in the Genus Verticillium

Abstract: The availability of genomic sequences of several Verticillium species triggered an explosion of genome-scale investigations of mechanisms fundamental to the Verticillium life cycle and disease process. Comparative genomics studies have revealed evolutionary mechanisms, such as hybridization and interchromosomal rearrangements, that have shaped these genomes. Functional analyses of a diverse group of genes encoding virulence factors indicate that successful host xylem colonization relies on specific Verticilliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
113
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 76 publications
1
113
0
Order By: Relevance
“…A deletion mutant of the Verticillium transcription regulator Vta2 , which controls expression of 125 secreted proteins, failed to colonize plants and induce disease symptoms, indicating a role in pathogenicity (Tran et al, 2014), and the genome of two strains of the vascular wilt fungus V. dahliae , VdLs.17 and JR2, isolated from lettuce and tomato, respectively, have been sequenced (Klosterman et al, 2011; de Jonge et al, 2013). Comparative genomic analyses have also shown that V. dahliae has markedly increased secretion levels of pathogenic factors, including LysM effectors, NLPs, and an Ave1 virulence factor (Klosterman et al, 2011; de Jonge et al, 2012, 2013; Zhou et al, 2012; Santhanam et al, 2013; Klimes et al, 2015), in agreement with previous reports that the purified exoproteome of this pathogen can induce chlorosis and necrosis on the leaves of susceptible plants (Buchner et al, 1982, 1989; Nachmias et al, 1985; Meyer et al, 1994; Mansoori et al, 1995; Davis et al, 1998). These results all suggest that V. dahliae requires the presence of exoproteome virulence factors in order to infect host plants.…”
Section: Introductionsupporting
confidence: 90%
“…A deletion mutant of the Verticillium transcription regulator Vta2 , which controls expression of 125 secreted proteins, failed to colonize plants and induce disease symptoms, indicating a role in pathogenicity (Tran et al, 2014), and the genome of two strains of the vascular wilt fungus V. dahliae , VdLs.17 and JR2, isolated from lettuce and tomato, respectively, have been sequenced (Klosterman et al, 2011; de Jonge et al, 2013). Comparative genomic analyses have also shown that V. dahliae has markedly increased secretion levels of pathogenic factors, including LysM effectors, NLPs, and an Ave1 virulence factor (Klosterman et al, 2011; de Jonge et al, 2012, 2013; Zhou et al, 2012; Santhanam et al, 2013; Klimes et al, 2015), in agreement with previous reports that the purified exoproteome of this pathogen can induce chlorosis and necrosis on the leaves of susceptible plants (Buchner et al, 1982, 1989; Nachmias et al, 1985; Meyer et al, 1994; Mansoori et al, 1995; Davis et al, 1998). These results all suggest that V. dahliae requires the presence of exoproteome virulence factors in order to infect host plants.…”
Section: Introductionsupporting
confidence: 90%
“…It then employs various mechanisms to move through the root cortex into the plant vascular system, allowing for further colonization of the plant. When the fungus has completely infected the plant, it produces microsclerotial spores that remain stable and dormant in the soil until they are exposed to a new host [53]. To breed new cotton varieties resistant to Verticillium wilt, more research is required to identify resistance-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent soil-borne fungal pathogens comprise Fusarium oxysporum (Michielse and Rep, 2009), Verticillium spp. Klosterman et al, 2009;Klimes et al, 2015) and Rhizoctonia solani (Gonzalez et al, 2011), whereas the most notorious oomycetes include Phytophthora spp. (van West et al, 2003; and Pythium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Verticillium wilts are vascular wilt diseases caused by soil-borne fungal pathogens that belong to the Verticillium genus Klimes et al, 2015). Although Verticillium wilt symptoms may vary considerably between plant hosts, the most frequently observed symptoms of Verticillium wilt include stunting, wilting, chlorosis, necrosis, vascular discoloration and early senescence .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation